Review of the Genus Paracrias (Hymenoptera, Eulophidae, Entedoninae) - Gumovsky, A.V. (Вестник зоологии, 2001)
The New World genus Paracrias is reviewed, its diagnostic characters are corrected and the introgeneric variations are discussed. 13 species are recognized for the genus, 6 of them are described as new: P. huberi sp. n., P. laticalcar sp. n. and P. canadensis sp. n. from Canada, P. schauffi sp. n. from Mexico, P. woldai sp. n. and P. panamensis sp. n. from Panama). Diagnostic characters of the new species, change the concept of the genus. Entedon antander Walker treated earlier under Paracrias (LaSalle & Schauff, 1991) removed to the genus Horismenus. New geographic records are given. Key to species of the genus is provided. Проведен обзор распространенного в Новом Свете рода Paracrias, его диагностические признаки откорректированы и обсужден расброс признаков внутри рода. 13 видов указаны для Paracrias, 6 из них описаны впервые: P. huberi sp. n., P. laticalcar sp. n. и P. canadensis sp. n. из Канады, P. schauffi sp. n. из Мексики, P. woldai sp. n. и P. panamensis sp. n. из Панамы). Диагностические признаки новоописанных видов изменили концепцию рода Paracrias. Entedon antander Walker, включавшийся ранее в род Paracrias (LaSalle & Schauff, 1991), перемещен в род Horismenus. Для видов рода Paracrias в статье приведены новые местонахождения и таблицы к определению.